1993
DOI: 10.1002/bem.2250140505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 60 Hz electric and magnetic fields on the development of the rat cerebellum

Abstract: The effects of extremely low frequency (ELF) electromagnetic (EM) fields on the maturation of the rat cerebellum were studied. Newborn rats were exposed to 60 Hz electric and magnetic fields under three different combinations in a specially constructed apparatus. The pups were irradiated for 7-8 h daily, with a 30-min interruption for nursing. Pups were kept with their mothers for the remainder of the time. After approximately 1, 2, or 3 weeks of exposure, the pups were killed. Control pups were sham exposed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Several studies have tested the effects of electromagnetic fields on neuronal process outgrowth and nerve regeneration, with mixed results (Blackman et al, ; Gona et al, ; Drucker‐Colin et al, ; Greenebaum et al, ; Macias et al, ; Shah et al, ; Schimmelpfeng et al, ; Zhang et al, ; Kim et al, ; Baptista et al, ; Koppes et al, ), perhaps as a result of the variety of signal configurations, culture conditions, or injury paradigm. To investigate the effects of this PEMF signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have tested the effects of electromagnetic fields on neuronal process outgrowth and nerve regeneration, with mixed results (Blackman et al, ; Gona et al, ; Drucker‐Colin et al, ; Greenebaum et al, ; Macias et al, ; Shah et al, ; Schimmelpfeng et al, ; Zhang et al, ; Kim et al, ; Baptista et al, ; Koppes et al, ), perhaps as a result of the variety of signal configurations, culture conditions, or injury paradigm. To investigate the effects of this PEMF signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that ELF-MF affects human cognition and electrophysiology (Cook et al, 2002). ELF-MF may interfere with the activity of the brain (Bawin et al, 1996;Bruner and Harvey, 1998;Gona et al, 1993;Gundersen et al, 1986;Jenrow et al, 1998), and may generate behavioral and cognitive disturbances (Lai et al, 1993;Cuccurazzu et al, 2010;Mostafa et al, 2002;Gerth et al, 1983;Lai, 1996;Lai et al, 1998;Levine et al 1995;Lyskov et al 1996). These pronounced effects are found to interfere with memory performance (Mostafa et al, 2002;Lai et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, biological effects of RF‐EMF and their consequences on human health are receiving increasing scientific interest and have now become an urgent problem. Hematological , pathological , cardiac , endocrine , reproductive , and nervous changes , and also oxidative stress , cataract , and behavioral alterations due to EMF exposure have been evaluated previously by in vivo and in vitro studies. Some recent studies using newer techniques such as immunohistochemistry have investigated effects of radiation exposure on specific proteins .…”
Section: Introductionmentioning
confidence: 99%